2017
DOI: 10.1007/s11252-017-0697-7
|View full text |Cite
|
Sign up to set email alerts
|

Ground beetle (Coleoptera: Carabidae) communities on green roofs in Switzerland: synthesis and perspectives

Abstract: Green roofs have recently gained recognition for their potential contribution to urban ecosystems by providing, among other services, habitat for plants and animals, and stepping stones for mobile organisms, thereby enhancing permeability among habitat patches across densely built cities. In Switzerland, investigations over the past 20 years on more than one hundred distinct green roofs across six cities have provided an unprecedented dataset on ground beetles, albeit with information that is scattered across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…As has been found with several other invertebrate taxa [2,27,32], the species inhabiting green roofs tend to be widespread, generalist and disturbance-adapted species. The same studies also show that just a few species tend to dominate in terms of total abundance and being the most widespread among green roof habitats.…”
Section: Comparison To Other Green Roof Faunasupporting
confidence: 62%
See 1 more Smart Citation
“…As has been found with several other invertebrate taxa [2,27,32], the species inhabiting green roofs tend to be widespread, generalist and disturbance-adapted species. The same studies also show that just a few species tend to dominate in terms of total abundance and being the most widespread among green roof habitats.…”
Section: Comparison To Other Green Roof Faunasupporting
confidence: 62%
“…On the other hand, our findings are similar for non-flying taxa. A review of 102 green roofs in Switzerland found just 91 ground beetle species [32].…”
Section: Comparison To Other Green Roof Faunamentioning
confidence: 99%
“…Studies have also confirmed the presence of arthropods, such as beetles, spiders, true bugs, hymenopterans (ants, bees, wasps), flies [50][51][52], springtails (up to 44 species) [53,54], and mites [55], in addition to fungi [54,55] and bacteria [56]. A recent review conducted in six Swiss cities over the past 20 years showed that 91 out of the 532 species (17%) known in Switzerland are represented on green roofs [57]. Roofs are also habitat for vertebrates.…”
Section: Are Green Walls and Green Roofs Large Enough For Supporting mentioning
confidence: 99%
“…With moisture being the limiting factor controlling plant growth, plants and fauna are mainly heliotropic, thermophilic, xerophilic or mesophilic, acidophilic and oligotrophic, and originate from grasslands and pioneer habitats, showing a wide variety of functional traits for pollination, dispersal, and reproduction [49,50,54,57]. …”
Section: Are Green Walls and Green Roofs Identical Habitats?mentioning
confidence: 99%
“…According to Tóthmérész et al [38], 50 species were found in forests nearby the city of Sfantu Gheorghe along rural-urban gradient (Romania). Over the past 20 years in six Swiss cities the 91 ground beetles species were recorded on green roofs [39]. In three woodlands in the City of Debrecen (Hungary) 50 species of carabid beetles were registered [40].…”
Section: Resultsmentioning
confidence: 99%